Enhancing water management in South Africa: the need for efficiency in monitoring and evaluation programmes - Richard Kwame Adom; Mulala Danny Simatele (Environmental Systems Research)
Abstract Water monitoring and evaluation form one of the key components of water reforms in South Africa post-1994. These reforms specifically, seek to improve water management, thus balancing water supply and demand, ensuring water quality and supplying water for the growing population and economy. While numerous laws and regulations, frameworks and institutions such as the Department of Water and Sanitation, the South African Local Government Administration, the Water Research Commission, the South African Association of Water Utilities and South African Human Rights Commission have been set up to meet these objectives, very little successes have been achieved. In some situations, there have been outright failure. These are attributed to overly complexities in the monitoring systems. Furthermore, there is lack of transformation in water management structures as well as insufficient data and information to make inform decisions. This paper uses a participatory data collection approach of qualitative and quantitative methods and extensive literature to explore the complexities of monitoring and evaluating water activities in post-independence South Africa. Our findings uncovered that there is conflicting views between the top-down monitoring approach currently used against a broad participatory monitoring strategy. To address these challenges this paper proposes establishing clear performance indicators, investing in data collection and management systems, strengthening institutional capacity, and promoting stakeholder participation. Additionally, we suggest using innovative monitoring techniques, implementing regular assessments and reviews, enhancing transparency and accountability and integrating monitoring and evaluation into planning processes.